A new method to optimize resection area using a radiation treatment planning system and deformable image registration for breast-conserving surgery after neoadjuvant chemotherapy. Issue 4 (April 2021) - Miyoshi, Tetsutaro; Yamaguchi, Satoshi; Fujimoto, Hiroshi; Yoshioka, Shigeru; Shiobara, Masayuki; Wakatsuki, Kazuo; Suda, Kosuke; Miyazawa, Kotaro; Aida, Toshiaki; Watanabe, Yoshihiro; Otsuka, Masayuki
Abstract: Background: We devised a breast-conserving surgery (BCS) utilizing a new image-processing and projection technique using a radiation treatment planning system (RTPS) and deformable image registration (DIR) for patients with breast cancer after neoadjuvant chemotherapy (NAC). RTPSs and DIR are commonly used in planning radiation treatment. The purpose of this pilot study was to evaluate the feasibility of our procedure. Patients and methods: Twenty-six patients diagnosed with breast cancer underwent NAC and BCS between November 2014 and May 2020. Multidetector-row computed tomography was performed in the same position used for surgery before and after NAC. In the DIR, CT before NAC was fused to CT after NAC. The RTPS simulated the design of tumor excision, and excision area was projected onto the breast skin utilizing an irradiation device. Results: In 26 patients with breast cancer after NAC, BCS was performed using the processing and projection technique of the RTPS with DIR. Only 1 of 26 patients showed carcinoma present in the surgical margins, and subsequently developed ipsilateral breast tumor recurrence. Mean excised volume was 33.5 cm 3 (range, 12.8–62.8 cm 3 ), and percent breast volume excised was 6.8% (range, 2.5–15.7%). Conclusions: This pilot study confirmed the simplicity and utility of our procedure for minimally invasive BCS in patients with breast cancer after NAC. We will keep evaluating the safety and efficacy of our procedure in more patients.